Nurses’ knowledge, attitudes, and practice with regards to nutritional management of diabetes mellitus - Mahsa Farzaei; Shahla Shahbazi; Neda Gilani; Alireza Ostadrahimi; Leila Gholizadeh (BMC Medical Education, 2023)
Abstract Background The prevalence of diabetes is increasing rapidly worldwide. Nurses work collaboratively with multidisciplinary teams to improve diabetes management. Yet, little is known about nurses’ role in nutritional management of diabetes. This study aimed to evaluate nurses’ knowledge, attitudes, and practice (KAP) toward nutritional management of diabetes. Methods This cross-sectional study was conducted with 160 nurses, who were recruited between July 4 and July 18, 2021 from two referral tertiary teaching hospitals in Iran. A validated paper-based self-reported questionnaire was used to assess nurses’ KAP. Data were analyzed using descriptive statistics and multiple linear regression analysis. Results The mean knowledge score of nurses about nutritional management of diabetes was 12.16 ± 2.83, and 61.2% showing a moderate knowledge level on nutritional management of diabetes. The mean attitudes score was 60.68 ± 6.11, with 86.92% of participants demonstrating positive attitudes. The mean practice score of study participants was 44.74 ± 7.81, with 51.9% having a moderate level of practice. Higher knowledge scores were observed among male nurses (B = -7.55, p = 0.009) and those with blended learning as a preferred learning method (B = 7.28, p = 0.029). Having an opportunity to provide education to patients with diabetes during shifts affected nurses’ attitudes positively (B = -7.59, p = 0.017). Practice scores were higher among nurses who perceived themselves competent in the nutritional management of diabetes (B = -18.05, p = 0.008). Conclusion Nurses’ knowledge and practice in the nutritional management of diabetes should be increased to help improve the quality of the dietary care and patient education they provide these patients. Further studies are needed to confirm the results of this study both in Iran and internationally.